Impact of Sports Culture Education on College Students’ Psychological Tolerance - Jiali Liu; Kun Hou (Revista de Psicología del Deporte (Journal of Sport Psychology), 2024)
In order to better understand the impact of sports culture education on the psychological resilience of college students, the author proposes a study based on the impact of sports culture education on the psychological resilience of college students.A stratified random sampling method was used to select 160 students from the new campus group and 130 students from the west campus group from the 2020 level students of a certain normal college as the test group and control group, respectively. By using literature review methods, questionnaire survey methods, interview methods, and pre and post-test methods, the psychological health status of the research subjects was measured. The mental health questionnaire uses the Symptom Checklist 90 (SCL-90). The measurement time is from September 2020 to June 2022, which is two academic years. A comparative analysis was conducted on the relationship between the mental health level of college students and campus sports culture, and the relationship between the mental health level and campus sports culture was explored.The research results show that a good campus sports culture can create a huge psychological atmosphere, enabling students to have positive emotional experiences, develop a strong interest in sports, stimulate their strong learning motivation, and actively participate in physical exercise. There is an extremely close relationship between physical exercise and mental health, physical exercise has an undeniable positive effect on promoting the level of mental health in the human body, can cultivate their spirit of struggle，and can improve the overall mental health level of college students. Conclusion: A good campus sports cultural atmosphere has a certain positive significance and role in improving the overall mental health level of college students.